KETIDAKPUASAN BENTUK TUBUH DENGAN PSYCHOLOGICAL WELL-BEING PADA WANITA DEWASA AWAL YANG SUDAH MEMILIKI ANAK - Niawana Br Bangun (Bajang Institute, 2023)
Body shape dissatisfaction is often experienced by early adult women who already have children. Kartikasari (2013), found a relationship between body dissatisfaction and psychological well-being. Psychological well-being defined as the full realization/achievement of an individual's potential. It is then that a person can fully accept their strengths and weaknesses. The purpose of this study was to determine the relationship between body dissatisfaction and psychological well-being in early adult women who have had children, using a quantitative correlation approach. The number of participants was 69 early adult women with children. This study uses a scale of body dissatisfaction and psychological well-being, with the result that there is a significant postive between body dissatisfaction and psychological well-being.